Identidade Quilombola e as práticas pedagógicas no ensino fundamental da escola Santo André, município de Abaetetuba – Pará - SANTOS, Manuel Baia (2023)
The present research investigates the quilombola identity related to the pedagogical practices offered by the school in the minor elementary school through, among the data collection techniques were conducted interviews and dynamics of conversation wheel with the students of elementary education including the infantile education in which they were photographic records and gave a questionnaire to the teachers, in addition, we made the participant observation. We discuss the category identity as belonging and correlation with environment and territory in which they live. The research identified that it is necessary to value the quilombola identity of the community in a more effective way, not only in specific periods, but a permanent pedagogical political work and the school.